Measurement of Neutral-Current π$^0$ production for $ν_µ$ interactions in ND280 - Williamson, Z (2014)
This thesis presents a study of neutral-current π0 production from νµ interactions. The study uses data taken at the Tokai-to-Kamiokande off-axis experiment's near detector (ND280). Monte Carlo studies were used to develop selection criteria to reconstruct event signatures produced from such interactions. This physics analysis focuses on the tracker region of the ND280 subdetector. Other π0 analyses using different detector regions are either underway or completed. The physics analysis, after being developed from Monte Carlo studies, was then run on real data. This analysis goes partway towards measuring the neutral-current π0-producing neutrino interaction cross-section, by measuring the rate of such interactions in the T2K experiment's near detector, ND280. The observed results were: N NCπ0 Data (1) This rate measurement, when made as a ratio of the predicted Monte Carlo rate, yields a ratio of: (2) RData RMC = 1.20 ± 0.13stat ± 0.72syst